STRES DENGAN KUALITAS TIDUR PADA REMAJA - Pangestika, Ghina; Lestari, Dhian Ririn; Setyowati, Anggi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2018)
Most adolescent have problems with the quality ofsleep due to social demands such as academicdemands that contribute to stress. The aim of study to determine relationship between stress andsleep quality among adolescents in SMP Darul Hijrah Puteri. This study used cross sectionalcorrelation with total sample was 149 adolescents were taken using cluster random samplingtechnique on 23 December 2017. The instruments were questionnaires Educational Stress Scalefor Adolescent (ESSA) to assess stress and Pittsburgh Sleep Quality Index (PSQI) to assess sleepquality. Analyze result showed that stress among adolescents in SMP Darul Hijrah Puteriaverage of 54.83 and sleep quality with an average of 8. 26. In Spearman Rho’ analysis, there wasno correlation between stress and sleep quality among adolescents in SMP Darul Hijrah Puteri(p = 0.342, r=0.078). Several factors affect sleep quality, so the stress cannot be the only factorcausing problems in sleep quality.